Knowledge, attitudes and practices of voluntary HIV counselling and testing among rural migrants in central China: a cross-sectional study - Zhang, Tiejun (Oxford University Press, 2012)
Objective: To document knowledge, attitudes and practices of voluntary HIV counselling and testing (VCT) among rural migrants in central China. Methods: A cross-sectional study with face-to-face anonymous questionnaire interviews was conducted using a structured questionnaire. Results: Among 1280 participants, 87.9% reported having had sexual intercourse during their lifetime, with 69% of singles reporting having had sexual intercourse and 49.1% having had sex in the past month. Only 21% always used condoms, 84.4% knew HIV infection was diagnosed through blood testing, 56.6% had heard of VCT, but only 3.8% perceived their own risk for HIV infection. Only 43 (2.3%) had ever been tested for HIV, and none had ever been tested at a VCT site. About two-thirds (64.5%) would be willing to use VCT services upon awareness of HIV risk. A logistic regression model showed that females, those having little knowledge of HIV/AIDS, those unwilling to work with HIV-infected individuals, never having been tested for HIV and having low awareness regarding HIV risk were less willing to use VCT. Conclusions: The results of this study indicated that much greater efforts are needed to improve HIV/AIDS and VCT knowledge, to promote safer sex and to improve VCT acceptance among rural migrants in central China, particularly those engaging in risky behaviours.